PENGARUH KEPERCAYAAN DAN KEPUASAN ANGGOTA TERHADAP LOYALITAS ANGGOTA KSPPS - Kuncoro, Kuncoro; Prasojo, Eko (Program Studi Manajemen, 2023)
This study aims to determine the effect of trust and member satisfaction on member loyalty of KSPPS Tamzis Bina Utama, Godean Branch, Yogyakarta. The population used in this study were all members of Tamzis Bina Utama, Godean Branch, with a sample of 150 respondents. The sampling technique used convenience sampling technique. Data collection techniques using observation and a list of questions. The data analysis method used is validity and reliability test, classic assumption test, multiple regression analysis, hypothesis testing. The results of this study indicate that trust and satisfaction simultaneously have a positive and significant effect on the loyalty variable.